The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/23727322211068021
|View full text |Cite
|
Sign up to set email alerts
|

Improving School Outcomes for Transgender and Gender-Diverse Youth: A Rapid Review

Abstract: Transgender and gender-diverse students may experience poorer school outcomes due to a threatening school climate. A rapid review using systematic search found 2,111 studies mentioned LGBTQ + students, but only three were peer-reviewed empirical tests of potential interventions to improve school outcomes among transgender and gender-diverse youth: (a) Sexual orientation, gender identity, and/or gender expression ( SOGIE) inclusive policies were associated with greater school safety, less victimization, less so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Pollitt et al (2019) found that the consistent use of gender‐affirming names was a buffer to negative mental health symptoms for gender‐diverse youth. When youths' gender‐affirming names and pronouns were used in school environments, their mental health improved (Feijo et al, 2022). These data emphasize how imperative it is that gender‐affirming names and pronouns are used for gender‐diverse youth.…”
Section: Critical Discussionmentioning
confidence: 99%
“…Pollitt et al (2019) found that the consistent use of gender‐affirming names was a buffer to negative mental health symptoms for gender‐diverse youth. When youths' gender‐affirming names and pronouns were used in school environments, their mental health improved (Feijo et al, 2022). These data emphasize how imperative it is that gender‐affirming names and pronouns are used for gender‐diverse youth.…”
Section: Critical Discussionmentioning
confidence: 99%
“…When a transgender youth has even one supportive adult in their life, their mental health and academic outcomes can drastically improve (Fontanari et al, 2020). School staff can play a major role in helping transgender youth (Feijo et al, 2022). In fact, the United States Department of Education, along with several other national organizations (Table 2), endorse research-informed practices for school staff to use to support transgender youth (U.S. Dept.…”
Section: Introductionmentioning
confidence: 99%